2003
DOI: 10.1590/s1516-14392003000300017
|View full text |Cite
|
Sign up to set email alerts
|

Ageing of the DGEBA/TETA epoxy system with off-stoichiometric compositions

Abstract: An investigation was carried out on the room temperature ageing of off-stoichiometric DGEBA/TETA epoxy formulations. The results obtained show that the epoxy rich mixtures have their inherent brittleness increased by the ageing treatment due to recrystalization of the unreacted epoxy monomers, although homopolymerization could also play a minor role. The initial reaction steps dominated by the amine addition reactions control the macromolecular structure and the mechanical performance of the stoichiometric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…This weight loss phenomenon was also observed for other different polymeric systems and reported by several authors 2,[4][5][6][7][8][9][10][11][12] . In the work of Fraga et al 4 , weight loss was not observed in the curve of weight change, but the presence of voids detected after immersion and an analysis by FTIR pointed out the extraction of low molecular weight molecules.…”
Section: Hygrothermal Ageingsupporting
confidence: 84%
See 1 more Smart Citation
“…This weight loss phenomenon was also observed for other different polymeric systems and reported by several authors 2,[4][5][6][7][8][9][10][11][12] . In the work of Fraga et al 4 , weight loss was not observed in the curve of weight change, but the presence of voids detected after immersion and an analysis by FTIR pointed out the extraction of low molecular weight molecules.…”
Section: Hygrothermal Ageingsupporting
confidence: 84%
“…Few works on water absorption of vinyl ester resins presented the effect of the hygrothermal ageing on the mechanical properties of the neat resin 4,6,7 Materials Research and on the fracture surface 8 . Additionally, fracture surface appearance of epoxy systems has been studied [9][10][11] and has been correlated to the failure mechanisms 10 , although no similar studies have been found for vinyl-ester systems.…”
Section: Introductionmentioning
confidence: 99%
“…This was probably due to the presence of excess of epoxy resin in case of cr-SPAES-H-70. Since off-stoichiometric mixture contain latent sites [37], which could remain on the macromolecular structure and can become susceptible for the free radical attack.…”
Section: Methanol Permeability and Selectivitymentioning
confidence: 99%
“…The epoxy ring in POSS-glycidoxypropyl can also react with hydroxyl groups of a polyol, leading to the formation of ether groups (etherification). The effect of this reaction is insignificant below 150 • C [38,39]. The reaction of PU/POSSglycidoxypropyl was carried out at room temperature and post-cured at 80 • C, it 1426 T. Efrat et al …”
Section: Thermo-mechanical Analysismentioning
confidence: 99%